“Holding–Cuddling” and Sucrose for Pain Relief During Venepuncture in Newborn Infants: A Randomized, Controlled Trial (CÂSA) - Hoarau, Karole; Payet, Marie Line; Zamidio, Laurence; Bonsante, Francesco; Iacobelli, Silvia (Frontiers in Pediatrics, 2021)
Objectives: Oral sucrose is commonly used to provide analgesia to neonates during painful procedures, such as venepuncture. The additional benefits to reduce pain during venepuncture when oral sucrose is combined with non-pharmacological strategies, have not been extensively studied yet. This randomised-controlled trial compared the efficacy of oral sucrose with non-nutritive sucking versus oral sucrose with non-nutritive sucking plus “holding-cuddling” for pain management during venepuncture in term infants from birth to three months of life. Methods: Seventy-eight infants were equally randomized to receive 24% oral sucrose with non-nutritive sucking (control group) or 24% oral sucrose with non-nutritive sucking plus “holding–cuddling” (being held in a secure, cuddling position) (experimental group) before venepuncture. Behavioural response to pain was measured by the 0-10 ranking scale “acute pain for neonates (APN)”at 30”and 60’’after venepuncture. Results: Within the study sample, APN score were  2 for 32/68 (47%) infants. “Holding-cuddling” did not significantly reduce mean APN scores at 30”and 60”, but the rate of infants experiencing a high pain score (APN  8) at 60”after the venepuncture was significantly lower in the experimental group compared to controls 4/34 versus 12/34 (p=0.04). Conclusions: Venepuncture is a painful procedure in newborn and young infants. The implementation of behavioural strategies in association with oral sucrose may mitigate pain during this procedure.